Teacher Education Needs at the Tertiary Level of Education in India: Perceptions of Doctoral Students in the States of Assam and Nagaland - Awomi, Niboli (Voices of Teachers and Teacher Educators, 2023)
The study presents the perceptions of doctoral students in the states of Assam and Nagaland, regarding the need for teacher education programmes in Indian tertiary educational context. And to ascertain the purpose of this study, a needs analysis following Hutchinson and Waters' model (1987), has been adopted to understand the doctoral students' needs, wants, and lacks; grounding this concept as the basis, respondents' perceptions of the need for teacher education programmes finds congruence. The study has adopted a qualitative approach and a total of 25 doctoral students from universities in Assam and Nagaland responded to the study. Findings from respondents' needs analysis convey that across universities, doctoral studies emphasised the research aspect while giving less or no attention to the pedagogical aspect the two quintessentially interwoven aspects in the teaching profession. Therefore, the absence of pedagogical mentorship in the doctoral studies curriculum underpins respondents' perceptions of the need for teacher education programmes at the tertiary level of education in India.